7. Stylistic Considerations on Scene No. 8 from the Musical Performance PreȚioasele Ridicole [The Affected Young Ladies] by Vasile Spătărelu - Petrescu Alexandru Radu (Sciendo, 2021)
Molière is one of the playwrights who not only marked and defined the seventeenth century in France, but, creator of the modern comedy and discoverer of the authentic comic, contributed fully to educating the public in his present and for the future. His comedies have stood the test of time, as they resonated with the audience, which found itself in them. In the twentieth century, his plays entered the artistic territories adjacent to the theater trough other creators, who turned them into film scripts and librettos for musical theater. The subject of our research is a fragment pertaining to the farcePrețioasele ridicole [The Affected Young Ladies] turned into a musical show under the signature of Vasile Spătărelu. An important name in Romanian music, creator with great melodic imagination, harmonic refinement and perfect literary taste, the composer from Iași made a possible compositional model for the genre, which is part of the Romanian musical show's route opened by Paul Constantinescu and Pascal Bentoiu. His work is distinguished by the stylistic area to which it adheres, by rhythm and vivacity, by the original combination between the spoken and the sung text, by the ingenious architecture of the scenes, by the adequacy of the writing technique to the desired effect and expression. Fully requesting all the resources of the interpreters, we consider that the analysis of the important moments is very useful to them. If pages of theatrical exegesis were dedicated to the characters Magdelon and Cathos, for Mascaril we did not identify something similar, much less a stylistic-interpretive analysis from a musical perspective. In order to achieve a complete characterization of the character, useful to potential student performers, we will comment on the first segments of the Scene no.8 in which Mascaril's "identity" is established, as he presents himself in front of the two "precious ones". (the entrance and the monologue).